Pengaruh Struktur Modal terhadap Profitabilitas dengan Nilai Perusahaan sebagai Variabel Mediasi pada Perusahaan LQ45 di Bursa Efek Indonesia Periode 2021–2023 - Wahyudi, Bambang; Yuni Astuti, Fitria; Khafid, Abdul (Journal of Applied Accounting And Business, 2025)
This research seeks to examine how capital structure influences profitability, with firm value serving as a mediating variable, in LQ45 companies listed on the Indonesia Stock Exchange (IDX) throughout the 2021–2023 period. This study utilizes a quantitative method and relies on secondary data derived from the financial reports of 28 companies that have consistently been part of the LQ45 index. This study conducts its data analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM), which is operationalized through the SmartPLS 4 application. The findings indicate that firm value exerts a positive and significant influence on profitability, while capital structure positively influences firm value but negatively affects profitability. Furthermore, firm value is proven to mediate the relationship between capital structure and profitability. These findings support the Trade-Off Theory, emphasizing that an optimal balance of debt usage can enhance firm value, which subsequently strengthens profitability. The study provides theoretical implications concerning financial management practices and practical recommendations for managers, investors, and policymakers to optimize capital structure and improve corporate performance.